Insights into the molecular mechanisms of browning tolerance in luffa: a transcriptome and metabolome analysis - Wu, Shan; Sun, Miao; Lian, Huashan (Frontiers in Plant Science, 2025)
IntroductionEnzymatic browning significantly affects the edible, nutritional, and commercial value of luffa. Investigating the expression and regulation of key enzyme genes involved in the browning process is crucial for understanding the molecular mechanisms underlying luffa browning.MethodsFruit samples were collected at 15 (S1), 20 (S2), and 45 days (S3) after flowering from two contrasting luffa varieties: the browning-sensitive Long-quan-yi (LQY) and the browning-tolerant Jiang-du (JD). RNA-sequencing technology, combined with ultra-performance liquid chromatography electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS), was used to obtain transcriptome and metabolome data, which were subsequently analyzed using a series of bioinformatics approaches. Quantitative polymerase chain reaction (q-PCR) was used to validate gene expression.ResultsCompared with JD, the ROS levels and PPO activity were elevated in LQY. In the polyphenol metabolic pathway, 24 key enzyme genes including CuAO, PPO, and TDC, were identified. In the flavonoid metabolic pathway, 57 key structural genes, such as PAL, C3H, and 4CL, were identified. These genes showed different expression patterns between the two luffa varieties. Differentially expressed genes were mainly involved in the regulation of 34 MYB, 15 bHLH, 19 WD40, and 14 WRKY transcription factors. Further metabolomics analysis showed that the levels of polyphenol metabolites were upregulated in LQY, whereas the levels of flavonoid metabolites were upregulated in JD.DiscussionThis study integrated transcriptomic and metabolomics data to identify key genes, transcription factors and metabolic pathways associated with luffa browning. q-PCR analysis was performed to validate the expression of POD and MYB genes. These findings provide a theoretical foundation for further investigation into the molecular mechanisms underlying luffa browning and offer potential targets for genetic improvement or breeding strategies to enhance luffa quality.